Re-bordering education: Embracing resilience in addressing refugee students’ precarity in South African higher education amidst global crises - Otilia Chiramba (Perspectives in Education)
Research into refugee studies is vital because this group grapples with their identity in society and their experiences as they strive to overcome the challenges they encounter in higher education. This paper is based on a combination of existing literature and empirical evidence from a PhD thesis, where data was collected through unstructured interviews with refugee students that provided in-depth narratives. It focuses on how refugee experiences of improving their qualifications through universities in their host countries became a crisis due to inadequate institutional support mechanisms that replicated the harsh experiences they faced in broader society. The paper highlights that despite some dire refugee experiences, these formed an important foundation for their resilience. The paper’s key findings point to the inadequate support mechanisms for refugees in universities and how this reflects the broader societal support limitations. Instead of categorising the refugees as victims, the paper points to their experiences as essential in shaping their resilience. This paper concludes that the holistic experiences of the refugees throughout the migration trail, from planning to leave their country to their experience of the education system and broader society in the host country, ought to be viewed as an integral part of forming their resilience.